2014
DOI: 10.1002/ajp.22361
|View full text |Cite
|
Sign up to set email alerts
|

High dietary diversity supports large group size in Indo‐Chinese gray langurs in Wuliangshan, Yunnan, China

Abstract: Identifying ecological factors underlying primate group size has been a central theme in primate behavioral ecology. The ecological constraints model proposes that increased group size leads to enhanced within-group feeding competition, necessitating increased travel to encounter additional or more productive feeding sites. Over the course of three years, we studied the largest known group (>80 individuals) of Trachypithecus crepusculus (Indo-Chinese gray langur) for 1738 hours during 213 days (including 96 fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…A study made on the largest known group of Trachypithecus crepusculus found similar results with larger total HR but no increase in DPL when compared with other groups. Instead, the authors suggested that high dietary diversity enables to support large group size by decreasing within‐group feeding competition (Pengfei et al, 2014). We suggest here that plantations with large clumps of high‐quality seeds provide enough food in quality, quantity, and for long enough time to sustain such a large troop in Sakaerat.…”
Section: Discussionmentioning
confidence: 99%
“…A study made on the largest known group of Trachypithecus crepusculus found similar results with larger total HR but no increase in DPL when compared with other groups. Instead, the authors suggested that high dietary diversity enables to support large group size by decreasing within‐group feeding competition (Pengfei et al, 2014). We suggest here that plantations with large clumps of high‐quality seeds provide enough food in quality, quantity, and for long enough time to sustain such a large troop in Sakaerat.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to previous studies of chimpanzee dietary diversity (Wrangham et al, 1998;Fawcett, 2000), the diet of the Waibira community increased in diversity when food was more abundant, albeit not at a significant level. This might be a way of maintaining a larger overall community size as has been suggested for a group of Indo-Chinese grey langurs (Trachypithecus crepusculus) in Wuliangshan, China (Pengfei et al, 2015). The group of langurs studied was 3-10 times larger than other groups of this species, yet it did not travel greater distances per day or devote more time to travel.…”
mentioning
confidence: 73%
“…Mean daily path length was also not correlated with group size in five groups of black-and-white colobus (Colobus guereza), although the largest group exhibited the longest mean daily path length (Fashing, 2001). More recently, Pengfei et al, (2015) reported that daily path length in Indo-Chinese grey langurs (Trachypithecus crepusculus) did not increase with group size but remained relatively constant even when explicit monthly changes in dietary pattern occurred.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
See 2 more Smart Citations